The improvement of the special legislation in the sphere of anti-crisis administrative-legal regulation of the economy of Ukraine - Крикун, Віктор Борисович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The author has carried out a research of the special normative acts (both legislative and subsidiary nature) the norms of which constitute the legal basis for administrative and legal anti-crisis regulation. The author has analyzed special normative acts in this sphere, and also has proposed and justified a list of proposals for their improvement.